TOO YOUNG TO CARRY: UNDERSTANDING THE DOUBLE BURDEN OF ANEMIA AND EARLY PREGNANCY AMONG ADOLESCENTS IN RURAL TANGERANG - Trisna Amerdista; David Christian; Indri; Muhammad Ikmal Syafii (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Background: Anemia during pregnancy continues to be a significant public health concern, especially among adolescents in low-resource settings. This study examines the prevalence of anemia among pregnant adolescents (<20 years) in Cisoka Puskesmas, Indonesia. Methods: Employing a cross-sectional design with total sampling, we examined medical records from January to December 2024. Hemoglobin levels were measured using Onemed HbCheck Hemoglobin Test Meter, with anemia defined as Hb <11.0 g/dL. Descriptive statistics were analyzed using SPSS 26. Results: Among 76 participants, the prevalence of anemia was 46.1%, peaking in the third trimester (54.3%). Mean hemoglobin levels showed a notable decline across trimesters (11.48 g/dL in the first trimester to 10.43 g/dL in the third trimester). Most participants (67.1%) had inadequate antenatal care (<4 visits). Moderate anemia predominated (51.4%), particularly in the second trimester (62.5%). Conclusion: This study reveals high anemia prevalence among pregnant adolescents in rural Tangerang, closely linked to advanced gestation and inadequate antenatal care. These results highlight the necessity for adolescent-specific iron supplementation and enhanced antenatal services for this vulnerable population.